High-performance alloy steel and preparation method thereof

By introducing a nano-scale carbon-oxygen composite second phase into high-performance alloy steel, the problem of insufficient radiation resistance after redissolution and neutron irradiation in high-temperature environments is solved, and the effect of significantly improving the high-temperature mechanical properties and radiation resistance is achieved.

CN119753515APending Publication Date: 2025-04-04TSINGHUA UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411997605.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The problem of resolving existing reactor steel in high temperature environments and the diffusion and resolving of nanooxides after neutron irradiation leads to insufficient irradiation resistance.

Method used

A high-performance alloy steel containing a nano-scale carbon-oxygen composite second phase consisting of carbon elements, oxygen elements and other metal elements, has high temperature creep stability and neutron radiation stability, and is able to form a co-uniform or semi-uniform interface with the matrix.

Benefits of technology

The high-temperature mechanical properties and radiation resistance of high-performance alloy steel are significantly improved, making it have stronger comprehensive performance under extreme conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753515A_ABST
    Figure CN119753515A_ABST
Patent Text Reader

Abstract

The invention relates to high-performance alloy steel and a preparation method thereof. The high-performance alloy steel comprises a matrix and a carbon-oxygen composite second phase, wherein the carbon-oxygen composite second phase is composed of a carbon element, an oxygen element and at least one other metal element selected from yttrium, titanium, tantalum, scandium, vanadium, scandium, zirconium and lanthanide. The alloy steel contains the carbon-oxygen composite second phase with high-temperature creep stability and neutron irradiation stability, so that the high-temperature mechanical property and the irradiation resistance of the high-performance alloy steel are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of steel materials, and in particular, relates to a high-performance alloy steel containing a carbon-oxygen composite second phase and a preparation method thereof. Background Art

[0002] Nuclear energy is an important component of the future energy system of mankind, and the blanket structure of advanced reactors is an important component of advanced reactors. The blanket directly faces the plasma and has a very harsh service environment. It needs to face high neutron radiation doses and high temperature environments. Therefore, the blanket material has extremely high requirements for radiation resistance and high-temperature mechanical properties.

[0003] Reactor steel is currently the primary candidate material for the cladding. In traditional research, the nano-second phase in steel is mainly composed of MX phase (M = Ta, V, Nb, Ti, Zr, etc.; X = C, N) or nano-oxide (TiO, TiO2, Y2O3, SiO2 and Y2TiO7, etc.). Among them, the MX phase is usually a face-centered cubic structure (FCC) with excellent radiation resistance; and the O element in the nano-oxide has an extremely low solid solubility in the steel matrix, only 0.0002wt.%, and is not easy to dissolve back into the matrix under high temperature conditions, so it has excellent high-temperature mechanical properties. For example, CN118621228A discloses ODS (oxide dispersion strengthened) steel strengthened with TiN and Y2O3, and points out that it has excellent high-temperature strength, high thermal stability and resistance to strong neutron irradiation.

[0004] However, C or N elements still have a relatively high solid solubility in the steel matrix. Under high temperature conditions, the MX phase is more likely to dissolve back into the matrix, resulting in insufficient high-temperature mechanical properties. In addition, the crystal structure of nano-oxides is complex and usually cannot form a coherent interface with the matrix. Therefore, after long-term neutron irradiation, the elements in the nano-oxides will diffuse back into the matrix, causing the nano-oxides to disappear, resulting in insufficient radiation resistance. Therefore, it is urgent to develop a high-performance alloy steel containing a new carbon-oxygen composite nano-second phase with a coherent or semi-coherent interface with the matrix, so that the reactor steel has both excellent radiation resistance and high-temperature mechanical properties.

[0005] References

[0006] Patent document 1: CN118621228A Summary of the invention

[0007] Problem that the invention aims to solve

[0008] The object of the present invention is to provide a high-performance alloy steel and a preparation method thereof, wherein the high-performance alloy steel comprises a carbon-oxygen composite second phase. The carbon-oxygen composite second phase has both high-temperature creep stability and neutron irradiation stability, and can significantly improve the high-temperature mechanical properties and radiation resistance of the high-performance alloy steel.

[0009] Solutions for solving problems

[0010] In order to solve the above problems, the present invention provides a high performance alloy steel containing a nano-scale carbon-oxygen composite second phase.

[0011] Specifically, the present invention provides a high-performance alloy steel, which comprises a matrix and a carbon-oxygen composite second phase, wherein the carbon-oxygen composite second phase is composed of carbon elements, oxygen elements and other metal elements, and the other metal elements are at least one of yttrium (Y), titanium (Ti), tantalum (Ta), scandium (Sc), vanadium (V), scandium (Hf), zirconium (Zr) and lanthanide elements.

[0012] According to the high performance alloy steel of the present invention, the other metal element is titanium.

[0013] According to the high performance alloy steel of the present invention, the carbon-oxygen composite second phase is formed by supersaturated solid-dissolved oxygen atoms, carbon atoms and other metal element atoms co-precipitating in the solid phase.

[0014] According to the high performance alloy steel of the present invention, the atomic distribution of carbon and oxygen elements in the carbon-oxygen composite second phase is disordered.

[0015] According to the high performance alloy steel of the present invention, the carbon-oxygen composite second phase forms a coherent or semi-coherent interface with the matrix.

[0016] According to the high performance alloy steel of the present invention, the size of the carbon-oxygen composite second phase is 1-200 nm.

[0017] According to the high performance alloy steel of the present invention, the size of the carbon-oxygen composite second phase is 2-10 nm, and the number density is more than 10 21 / m 3 .

[0018] According to the high performance alloy steel of the present invention, the carbon-oxygen composite second phase does not have a fixed stoichiometric ratio.

[0019] According to the high-performance alloy steel described in the present invention, the high-performance alloy steel contains carbon, oxygen and other metal elements, and the balance is Fe and inevitable impurity elements, wherein, based on the total weight of the alloy steel, the content of oxygen is 0.05-0.3wt.%, the content of carbon is 0.03-1.0wt.%, and when there is more than one type of other metal elements, the content of each other metal element is 0.3-5.0wt.%.

[0020] The present invention also provides a method for preparing the high performance alloy steel of the present invention, which comprises the following steps:

[0021] 1) Melting the raw steel to obtain liquid raw steel;

[0022] 2) Introducing oxygen into the liquid raw steel;

[0023] 3) Take 10 3 The solidification rate of K / s or more causes the liquid raw steel to solidify, forming a supersaturated solid solution of oxygen elements. The supersaturated solid solution of oxygen atoms, carbon atoms and other metal element atoms precipitate together in the solid phase to form a carbon-oxygen composite second phase.

[0024] Effects of the Invention

[0025] The high-performance alloy steel of the present invention contains a high-density dispersed nano-scale carbon-oxygen composite second phase, which has both high-temperature creep stability and neutron irradiation stability, significantly improving the high-temperature mechanical properties and radiation resistance of the high-performance alloy steel, and enhancing the comprehensive performance of the steel under extreme conditions. The high-performance alloy steel of the present invention provides a solution for advanced reactor materials and has broad application prospects. In addition to being used in advanced reactor materials, the high-performance characteristics of the high-performance alloy steel of the present invention also make it suitable for applications in other high-temperature and high-pressure environments, such as aerospace, energy, and chemical industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A flow chart of a preferred method for preparing the high performance alloy steel of the present invention;

[0027] Figure 2 The TEM image of the alloy steel-I obtained in Example 1 of the present invention shows a high-density dispersed nano-second phase, with the scale of the upper left image being 500 nanometers, the scale of the upper right image being 200 nanometers, and the scale of the lower left image and the lower right image being 100 nanometers;

[0028] Figure 3 Element distribution diagram of titanium oxycarbide of alloy steel-I obtained in Example 1 of the present invention;

[0029] Figure 4High-resolution TEM image and diffraction spot image of titanium oxycarbide of alloy steel-I obtained in Example 1 of the present invention;

[0030] Figure 5 EBSD diagram of Alloy Steel-I obtained in Example 1 of the present invention;

[0031] Figure 6 The high temperature tensile property test graph of the alloy steel-I obtained in Example 1 of the present invention and the high temperature creep property test graph of the alloy steel-I obtained in Example 1 and the alloy steel-I obtained in Comparative Example 1, wherein RT represents room temperature;

[0032] Figure 7 Morphology of titanium oxycarbide of Alloy Steel-I obtained in Example 1 of the present invention after irradiation;

[0033] Figure 8 TEM image of the alloy steel obtained in Comparative Example 1 of the present invention - Comparative Example I.

[0034] Explanation of reference numerals: 1-titanium oxycarbide, 2-ferrite. DETAILED DESCRIPTION

[0035] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.

[0036] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.

[0037] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0038] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0039] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0040] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0041] In this specification, "room temperature" or "normal temperature" means "10-40°C".

[0042] High performance alloy steel

[0043] The present invention provides a high-performance alloy steel, which comprises a matrix and a carbon-oxygen composite second phase, wherein the carbon-oxygen composite second phase is composed of carbon elements, oxygen elements and other metal elements, and the other metal elements are at least one of yttrium (Y), titanium (Ti), tantalum (Ta), scandium (Sc), vanadium (V), scandium (Hf), zirconium (Zr) and lanthanide elements.

[0044] The high-performance alloy steel of the present invention contains a high-density dispersed nano-scale carbon-oxygen composite second phase, which has both the high-temperature creep stability of nano-oxides and the neutron irradiation stability of MX phases, thereby significantly improving the high-temperature mechanical properties and radiation resistance of the material.

[0045] According to the high performance alloy steel of the present invention, the other metal element is preferably titanium or zirconium, and more preferably titanium.

[0046] The carbon-oxygen composite second phase is formed by the co-precipitation of metal elements, carbon elements and oxygen elements in the solid phase, which requires that the metal elements have a strong affinity with both carbon elements and oxygen elements. The affinity of titanium and zirconium elements with carbon elements is not significantly different from their affinity with oxygen elements, that is, the affinity of titanium / zirconium elements with carbon elements and oxygen elements is strong and similar, which further promotes the co-precipitation of titanium / zirconium elements with carbon elements and oxygen elements, and promotes the formation of the carbon-oxygen composite second phase.

[0047] According to the high-performance alloy steel of the present invention, the carbon-oxygen composite second phase is formed by supersaturated solid-dissolved oxygen atoms, carbon atoms and other metal element atoms co-precipitating in the solid phase. Supersaturated solid-dissolved oxygen atoms, carbon atoms and other metal atoms can co-precipitate in solid steel to form a high-density dispersed nano-scale carbon-oxygen composite second phase, thereby improving the high-temperature mechanical properties and radiation resistance of the steel.

[0048] According to the high performance alloy steel of the present invention, the atomic distribution of carbon and oxygen in the carbon-oxygen composite second phase is disordered, and the carbon or oxygen elements will not be concentrated in the center, periphery or one side of the nano second phase.

[0049] According to the high-performance alloy steel of the present invention, the carbon-oxygen composite second phase forms a coherent or semi-coherent interface with the matrix, which can improve its stability during neutron irradiation and improve the radiation resistance of the alloy steel.

[0050] According to the high performance alloy steel of the present invention, the size of the carbon-oxygen composite second phase is 1-200 nm.

[0051] According to the high performance alloy steel of the present invention, the size of the carbon-oxygen composite second phase is 2-10 nm, and the number density is more than 10 21 / m 3 The high-density dispersed nano-second phase is beneficial to improving the high-temperature creep performance of alloy steel.

[0052] According to the high performance alloy steel of the present invention, the carbon-oxygen composite second phase does not have a fixed stoichiometric ratio.

[0053] According to the high performance alloy steel of the present invention, the high performance alloy steel contains carbon, oxygen and other metal elements, and the balance is Fe and unavoidable impurity elements.

[0054] Among them, based on the total weight of alloy steel,

[0055] The content of oxygen element is 0.05-0.3wt.%, preferably 0.07-0.14wt.%.

[0056] The content of carbon element is 0.03-1.0wt.%, preferably 0.15-0.4wt.%.

[0057] When there are more than one other metal elements, the content of each other metal element is 0.3-5.0 wt.%, preferably 0.7-2.0 wt.%.

[0058] Furthermore, the high performance alloy steel of the present invention may further contain other metal elements, for example, one or more selected from Cr, W, Si or Mn.

[0059] Preparation method of high performance alloy steel

[0060] The present invention also provides a method for preparing the high performance alloy steel of the present invention, comprising the following steps:

[0061] 1) Melting the raw steel to obtain liquid raw steel;

[0062] 2) Introducing oxygen into the liquid raw steel;

[0063] 3) Take 10 3 The solidification rate of K / s or more causes the liquid raw steel to solidify, forming a supersaturated solid solution of oxygen elements. The supersaturated solid solution of oxygen atoms, carbon atoms and other metal element atoms precipitate together in the solid phase to form a carbon-oxygen composite second phase.

[0064] A small amount of oxidizing metal elements in the liquid raw steel will react with the oxygen element to form oxides, while a sufficient amount of oxidizing metal elements in the liquid raw steel will compete with the oxygen element, resulting in 10 3 Under solidification rate conditions above K / s, there is no time to form oxides, and ultimately supersaturated solid solution of oxygen atoms is formed in the solid steel.

[0065] The preparation method of the present invention can introduce sufficient oxygen into the liquid raw steel, and 3 A solidification rate of more than K / s can obtain a high-performance alloy steel with supersaturated solid dissolved oxygen atoms, thereby precipitating a carbon-oxygen composite second phase in the solid phase, improving the high-temperature mechanical properties and radiation resistance of the high-performance alloy steel.

[0066] Preferably, the high performance alloy steel of the present invention is manufactured by metal additive manufacturing technology, and more preferably, it is manufactured by laser powder bed fusion (LPBF) technology, such as Figure 1 As shown, the following steps are included:

[0067] preparing raw steel powder;

[0068] Adjusting the oxygen concentration in the printing chamber, preferably, controlling the oxygen concentration in the range of 300-10000 ppm, preferably in the range of 300-3000 ppm;

[0069] Preheating the substrate placed in the printing chamber, laying the raw steel powder on the substrate, and fully oxidizing the raw steel powder;

[0070] Laser forming is used to quickly melt the raw steel powder and 3 The solidification is carried out at a solidification rate of more than 0.04 K / s, thereby introducing sufficient oxygen into the molten pool after the raw steel powder is rapidly melted, and obtaining a high-performance alloy steel with supersaturated solid dissolved oxygen atoms.

[0071] Preferably, the substrate placed in the printing chamber is preheated to 300-1000°C, preferably 500-800°C.

[0072] Preferably, the time interval between laying the raw steel powder on the substrate and before laser forming is 2-60 s, preferably 4-20 s.

[0073] Example

[0074] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0075] Example 1

[0076] Based on the total weight of the high-performance alloy steel, the element composition of the high-performance alloy steel powder before preparation is as follows: Cr: 9%, W: 1%, Ti: 2.03%, C: 0.4%, Fe: bal. in mass percentage.

[0077] The preparation was carried out in the following steps:

[0078] Step 1: Using vacuum atomization powder making technology, the raw materials of Fe, Cr, W, Ti, and C are smelted according to the above formula to obtain raw steel powder;

[0079] Step 2: Use the SLM280 equipment to shape the raw steel powder using laser powder bed melting technology. Adjust the oxygen concentration in the printing chamber to control the oxygen concentration at 2000ppm;

[0080] Step 3: Preheat the substrate placed in the printing chamber to 540°C, evenly spread the raw steel powder obtained in step 1 on the substrate, and wait for 5 seconds for full oxidation.

[0081] Step 4: Start the laser to quickly melt and solidify the powder along the set path. The laser power is 200W, the scanning speed is 600mm / s, the scanning interval is 85μm, the layer thickness is 30μm, the rotation angle is 67°, and the scanning strategy is stripe mode. 5 K / s or more.

[0082] Step 5: The sample obtained in step 4 was cut from the substrate and recorded as Alloy Steel-I.

[0083] Example 2

[0084] Based on the total weight of the high-performance alloy steel, the element composition of the high-performance alloy steel powder before preparation is as follows: Cr: 9%, W: 1%, Ti: 1.08%, C: 0.25%, Fe: bal., in terms of mass percentage.

[0085] The preparation was carried out in the following steps:

[0086] Step 1: Using vacuum atomization powder making technology, the raw materials of Fe, Cr, W, Ti, and C are smelted according to the above formula to obtain raw steel powder;

[0087] Step 2: Use the SLM280 equipment to shape the raw steel powder using laser powder bed melting technology. Adjust the oxygen concentration in the printing chamber to control the oxygen concentration at 2000ppm;

[0088] Step 3: Preheat the substrate placed in the printing chamber to 540°C, evenly spread the raw steel powder obtained in step 1 on the substrate, and wait for 5 seconds for full oxidation.

[0089] Step 4: Start the laser to quickly melt and solidify the powder along the set path. The laser power is 200W, the scanning speed is 600mm / s, the scanning interval is 85μm, the layer thickness is 30μm, the rotation angle is 67°, and the scanning strategy is stripe mode. 5 K / s or more.

[0090] Step 5: The sample obtained in step 4 was cut from the substrate and recorded as alloy steel-II.

[0091] Comparative Example 1

[0092] Based on the total weight of the high-performance alloy steel, the element composition of the high-performance alloy steel powder before preparation is as follows: Cr: 9%, W: 1%, Ti: 2.03%, C: 0.4%, Fe: bal. in mass percentage.

[0093] The preparation was carried out in the following steps:

[0094] Step 1: Using vacuum atomization powder making technology, the raw materials of Fe, Cr, W, Ti, and C are smelted according to the above formula to obtain raw steel powder;

[0095] Step 2: Use the SLM280 machine to shape the raw steel powder using laser powder bed melting technology. Adjust the oxygen concentration in the printing chamber to control the oxygen concentration below 100ppm;

[0096] Step 3: Preheat the substrate placed in the printing chamber to 540°C, and evenly spread the raw steel powder obtained in step 1 on the substrate.

[0097] Step 4: Start the laser to quickly melt and solidify the powder along the set path. The laser power is 200W, the scanning speed is 600mm / s, the scanning interval is 85μm, the layer thickness is 30μm, the rotation angle is 67°, and the scanning strategy is stripe mode. 5 K / s or more.

[0098] Step 5: The sample obtained in step 4 was cut from the substrate and recorded as alloy steel-to-I.

[0099] Comparative Example 2

[0100] Based on the total weight of the high-performance alloy steel, the element composition of the high-performance alloy steel powder before preparation is as follows: Cr: 9%, W: 1%, Ti: 1.08%, C: 0.05%, Fe: bal., in terms of mass percentage.

[0101] The preparation was carried out in the following steps:

[0102] Step 1: Using vacuum atomization powder making technology, the raw materials of Fe, Cr, W, Ti, and C are smelted according to the above formula to obtain raw steel powder;

[0103] Step 2: Use the SLM280 equipment to shape the raw steel powder using laser powder bed melting technology. Adjust the oxygen concentration in the printing chamber to control the oxygen concentration at 2000ppm;

[0104] Step 3: Preheat the substrate placed in the printing chamber to 540°C, evenly spread the raw steel powder obtained in step 1 on the substrate, and wait for 5 seconds for full oxidation.

[0105] Step 4: Start the laser to quickly melt and solidify the powder along the set path. The laser power is 200W, the scanning speed is 600mm / s, the scanning interval is 85μm, the layer thickness is 30μm, the rotation angle is 67°, and the scanning strategy is stripe mode. 5 K / s or more.

[0106] Step 5: The sample obtained in step 4 is cut from the substrate and recorded as alloy steel-pair II.

[0107] The oxygen content in the obtained alloy steel was measured, and the measurement of oxygen element was carried out according to the standard "GB / T 11261-2006". Among them, based on the total weight of the alloy steel, the alloy steel-I contained 0.12wt.% of oxygen element, the alloy steel-II contained 0.13wt.% of oxygen element, the alloy steel-I contained 0.02wt.% of oxygen element, and the alloy steel-II contained 0.12wt.% of oxygen element.

[0108] TEM test

[0109] TEM tests were performed using a FEI Tecnai G2 F20 field emission transmission electron microscope operating at 200 kV.

[0110] The alloy steel-I obtained in Example 1 was subjected to TEM test, and the results are as follows Figure 2 As shown, the alloy steel-I obtained in Example 1 introduces a large amount of oxygen into the raw steel powder in situ during the additive manufacturing process, and obtains supersaturated solid solution of oxygen atoms, carbon atoms and titanium atoms through step 4, and finally forms high-density dispersed nano-carbon titanium oxide through coprecipitation. Among them, the size of the nano-carbon titanium oxide in the alloy steel-I is 5-10nm, and its number density is 1×10 23 / m 3 Similarly, the alloy steel-II obtained in Example 2 also contains high-density dispersed nano-carbon titanium oxide. The size of the nano-carbon titanium oxide in the alloy steel-II is 5-10nm, and its number density is 5×10 22 / m 3 .

[0111] The alloy steel obtained in Comparative Example 1 was subjected to TEM test, and the results are as follows: Figure 8 As shown, the alloy steel in Comparative Example 1 - Pair I does not contain high-density nano-scale titanium oxycarbide, but only contains a larger nano-second phase (MX phase) with a size of 50-100 nm.

[0112] The alloy steel obtained in Comparative Example 2 was subjected to TEM test, and it was found that it did not contain high-density nano-scale titanium oxycarbide, but only contained oxides with a size of 20-100 nm.

[0113] Element distribution test

[0114] The element distribution was tested using an electron energy loss spectroscopy (EELS) detector equipped in a double spherical aberration corrected transmission electron microscope.

[0115] like Figure 3As shown, based on the element distribution of alloy steel-I, it can be confirmed that nano-carbon titanium oxide with high density and dispersed distribution is formed in alloy steel-I. The alloy steel-II obtained in Example 2 has an element distribution similar to that of alloy steel-I, indicating that nano-carbon titanium oxide with high density and dispersed distribution is formed in alloy steel-II.

[0116] High resolution TEM test

[0117] High-resolution TEM measurements were performed on a FEI Tecnai G2 F20 field emission transmission electron microscope in high-resolution mode. The diffraction spots were obtained using the selected area electron diffraction function of the FEI Tecnai G2 F20 field emission transmission electron microscope.

[0118] The high-resolution TEM image and diffraction spot image of the titanium oxycarbide of alloy steel-I obtained in Example 1 of the present invention are as follows: Figure 4 As shown by Figure 4 It can be seen that the carbon-oxygen composite second phase of alloy steel-I forms a coherent or semi-coherent interface with the matrix. The nano-carbon titanium oxide of alloy steel-II obtained in Example 2 also has similar characteristics.

[0119] EBSD testing

[0120] EBSD data were collected using a TESCAN MIRA 3LMH thermal field emission scanning electron microscope equipped with an Oxford Instrument Symmetry electron backscattered diffraction (EBSD) probe, and analyzed and processed using Channel 5 software to obtain information such as band contrast images, orientation difference images, grain size, inverse pole figure distribution images, and inverse pole figures.

[0121] like Figure 5 As shown, the microstructure of Alloy Steel-I is ultrafine-grained ferrite with an average grain size of 1.12 μm and almost no anisotropy. Figure 5 The upper left figure is a contrast figure, the upper right three figures are the distribution diagrams of the inverse pole figures in the X, Y, and Z directions, the lower left is the orientation difference figure, and the lower right is the inverse pole figure. The texture strength of the sample is 1.18. The structure of the alloy steel-II obtained in Example 2 is an ultrafine-grained martensitic structure with an average grain size of 1.06μm and almost no anisotropy.

[0122] Tensile and creep properties

[0123] The room temperature tensile test was performed using a Shimadzu AG-X series electronic universal testing machine with a tensile rate of 0.3 mm / min and a strain rate of 10-3 / s. The length, width and thickness of the gauge section of the sample used in the tensile test are 5mm, 2mm and 1mm respectively. For the samples tested for tensile properties, each test is repeated at least three times to reduce the influence of experimental errors.

[0124] The high temperature tensile test was performed using an Instron 5966 electronic universal material testing machine with a tensile rate of 0.3 mm / min and a strain rate of 10 -3 / s, the test atmosphere is air, the test temperature is 300℃~700℃, and the holding time is 20min to ensure the uniform temperature of the sample. The gauge length, width and thickness of the sample used are 5mm, 1.5mm and 0.75mm respectively. For the samples tested for tensile properties, each is repeated at least 3 times to reduce the influence of experimental errors.

[0125] The high temperature creep performance of the samples was tested using the RDW-50 electronic creep endurance tester. The creep test used a 5mm diameter cylindrical sample in the RDJ-050.01-05 standard.

[0126] like Figure 6 As shown, the left figure is the high temperature tensile curve of alloy steel-I in Example 1, indicating that it has excellent high temperature strength, and the right figure is the high temperature creep curve of alloy steel-I in Example 1 and alloy steel-I in comparative example 1 under 650℃ / 120MPa conditions, and alloy steel-I exhibits excellent high temperature creep performance. The tensile strength of alloy steel-I at room temperature (RT), 600℃, 650℃, and 700℃ are 1110, 538, 441, and 331MPa, respectively. The tensile strength of alloy steel-II obtained in Example 2 at room temperature (RT), 600℃, 650℃, and 700℃ are 1538, 889, 563, and 370MPa, respectively. The creep lives of Alloy Steel-I, Alloy Steel-II, Alloy Steel-to-I and Alloy Steel-to-II at 650℃ / 120MPa are 788 hours, 635 hours, 90 hours and 110 hours respectively. It can be seen that the creep lives of Alloy Steel-I and Alloy Steel-II are significantly higher than those of Alloy Steel-to-I and Alloy Steel-to-II. In summary, the high-temperature mechanical properties of the alloy steels (Alloy Steel-I and Alloy Steel-II) containing a carbon-oxygen composite second phase in the embodiment are significantly better than those of the alloy steel containing only the MX phase (Alloy Steel-to-I) or the alloy steel containing only nano-oxides (Alloy Steel-to-II). The above results show that the high-temperature mechanical properties of the alloy steel containing a carbon-oxygen composite second phase of the present application are excellent.

[0127] Radiation resistance

[0128] Alloy steel-I and alloy steel-II were cut into 10mm×10mm×1mm specimens and heated at 650℃ and 1.84×10 16Ions / cm 2 Under the conditions of , single ion beam irradiation was performed using 2.5 MeV iron ions. Peak damage of 20 dPa was achieved at 700 nm below the sample surface. Subsequently, TEM testing was performed at this depth of the sample, and the specific test conditions of TEM were the same as described above.

[0129] like Figure 7 As shown, the alloy steel-I in Example 1 still maintains high density of nano-scale titanium oxycarbide after irradiation, and its number density does not decrease significantly, and its size does not increase significantly, showing its stability during irradiation. In contrast, the 20-100nm oxide formed in the alloy steel-II in Comparative Example 2 degraded during irradiation, and the oxide gradually dissolved. This is because the titanium oxycarbide forms a coherent interface with the matrix, showing excellent radiation resistance.

[0130] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.

[0131] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A high performance alloy steel, characterized in that: The high performance alloy steel comprises a matrix and a carbon-oxygen composite second phase, The carbon-oxygen composite second phase is composed of carbon, oxygen and other metal elements. The other metal element is at least one of yttrium (Y), titanium (Ti), tantalum (Ta), scandium (Sc), vanadium (V), scandium (Hf), zirconium (Zr) and lanthanide elements.

2. The high performance alloy steel according to claim 1, characterized in that: The other metal element is titanium.

3. The high performance alloy steel according to claim 1 or 2, characterized in that: The carbon-oxygen composite second phase is formed by supersaturated solid-dissolved oxygen atoms, carbon atoms and other metal element atoms co-precipitating in the solid phase.

4. The high performance alloy steel according to claim 1 or 2, characterized in that: The atomic distribution of carbon and oxygen elements in the carbon-oxygen composite second phase is disordered.

5. The high performance alloy steel according to claim 1 or 2, characterized in that: The carbon-oxygen composite second phase forms a coherent or semi-coherent interface with the matrix.

6. The high performance alloy steel according to claim 1 or 2, characterized in that: The size of the carbon-oxygen composite second phase is 1-200 nm.

7. The high performance alloy steel according to claim 1 or 2, characterized in that: The size of the carbon-oxygen composite second phase is 2-10 nm, and the number density exceeds 10 21 / m 3 .

8. The high performance alloy steel according to claim 1 or 2, characterized in that: The carbon-oxygen composite second phase does not have a fixed stoichiometric ratio.

9. The high performance alloy steel according to claim 1 or 2, characterized in that: The high performance alloy steel contains carbon, oxygen and other metal elements, and the balance is Fe and unavoidable impurity elements. Among them, based on the total weight of alloy steel, The content of oxygen element is 0.05-0.3wt.% The carbon content is 0.03-1.0wt.%, When there are more than one other metal elements, the content of each other metal element is 0.3-5.0 wt.%.

10. A method for preparing the high performance alloy steel according to any one of claims 1 to 9, characterized in that: The steps include: 1) Melting the raw steel to obtain liquid raw steel; 2) Introducing oxygen into the liquid raw steel; 3) Take 10 3 The solidification rate of K / s or more causes the liquid raw steel to solidify, forming a supersaturated solid solution of oxygen elements. The supersaturated solid solution of oxygen atoms, carbon atoms and other metal element atoms precipitate together in the solid phase to form a carbon-oxygen composite second phase.

Citation Information

Patent Citations

  • Nano titanium nitride and oxide composite reinforced ODS steel and preparation method thereof

    CN118621228A